Pasta pembersih gigitiruan bunga rosella (Hibiscus sabdariffa L.) menghambat pembentukan plak pada basis akrilik gigitiruan Denture cleanser paste of roselle flower (Hibiscus sabdariffa L.) inhibits plak formation on acrylic denture base - Moh. Dharmautama; Edy Machmud; Abdullah Mugan Maruapey (DiscoverSys Inc., 2013)
Roselle is a traditional medicinal herb that commonly found in Indonesia. Its ingredients are flavonoids, citric acid,malic acid, lactone, tartaric and antosian. Flavonoids are phenolic compounds that are fungistatic, fungisid andbacteriostatic. Extract of roselle extract has been observed by in vitro inhibit the formation of plaque in oral cavity.This study aimed to examine the effectiveness of pasta of roselle flowers as denture cleansers in inhibiting plaqueformation. Five acrylic full dentures and concentration of 2.5%, 5%, 7.5% and 10% denture cleansers pasta roselleflowers were used. Plaque score was calculated before and after the denture used with an interval of one week. Datawere analyzed using one-way ANOVA and Wilcoxon rank test. Roselle flower toothpaste at a concentration of 2.5%,5%, 7.5% and 10% significantly inhibited plaque formation and there was an effect of different concentrations of pastato the number of plaques (p<0.05). It was concluded that paste of roselle flowers as denture cleaning inhibit theformation of plaque effectively with a minimum concentration was 2.5%, although the most effective concentration ofrosella flower paste as denture cleaning pastes was 10%